Transformer mechanical integrity evaluation via unsupervised neural network (UNN) in smart grid network - Bohari Z.H.; Jali M.H.; Baharom M.F.; Nasir M.N.M.; Fariz N.M.; Thayoob Y.H.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Biomedical engineering; Computer networks; Condition monitoring; Conformal mapping; Control systems; Electric power transmission networks; Self organizing maps; Chinese Standard; Contingency analysis; Electrical systems; Integral part; Mechanical integrity; Smart grid; Smart grid networks; Unsupervised neural networks; Smart power grids